Quais os impactos do Prouni sobre as trajetórias laborais dos graduados no ensino superior? Um estudo de caso focado em salários de graduados em direito, medicina e engenharia da universidade positivo - André Gambier Campos; Roberto di Benedetto; Luiz Pereira Pinheiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The main question behind this article is: does the University for All Program (Prouni) promote better professional trajectories, which result in higher salaries for its beneficiaries? The salaries of the graduates who were employed show that those who went to college through Prouni had a more precarious insertion. Nonetheless, contrary to what may seem at first glance, this does not necessarily demonstrate a failure of this program to promote better occupational trajectories. After all, the variation of salaries before and after college graduation shows that there were salary advances for both groups, beneficiaries and non-beneficiaries of Prouni. However, in the case of the beneficiaries, this advance seems to have been significantly larger.
Keywords: I20; I23; I26; I28; 330; Prouni; colleges; salaries